The Impact of Gender on Food Waste at the Consumer Level (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
Food waste is one of the main contributors to economic disparities, social inequalities and environmental pollution. Numerous studies have sought to understand the drivers of food waste at various stages in the food supply chain, including the consumption stage. Based on a quantitative analysis of 252 Romanian consumers, the present study shows that gender is an important factor that affects the individuals’ attitudes and behaviours in regard to food and a potential factor that could affect the amount of food wasted. The study found that attitudes towards food waste evolve as individuals age, and that, at each stage, women tend to be more concerned about the negative impact of food waste on social equity or the family budget than men. In addition, women were found to display behaviours in regard to food acquisition and preparation that can result in higher food waste in a larger degree than men, even though the study found no differences in the actual amount of food wasted by the two genders. The results of the study are important because they show the need to adapt the public awareness campaigns on food waste on the particularities of each gender across several age groups.